Review Selaginella's Potential for Anticancer - amin, Rosa; Faghfirlie; Maryati; Primada Hari Anugrahini, Cita (Universitas Muhammadiyah Surakarta, 2024)
Selaginella is a popular herbal remedy for its antioxidants, anticancer, anti-inflammatory, and chemopreventive properties. Several studies have reported Selaginella's potential as an anticancer and co- chemotherapy agent. This narrative review aims to investigate Selaginella's potential as an anticancer agent and co-chemotherapy with doxorubicin. Studies were retrieved from PubMed, Science Direct, and Google Scholar databases. In total, 27 articles were selected. The results showed that Selaginella extract had cytotoxic activity against cancer cells T47D, MCF-7, A549, LLC, HeLa, Bel-7402, HT-29, 7721, P-388, and NCI- H460. One of the compounds contained and studied its mechanism is amentoflavone. Amentoflavone induces cell cycle arrest and apoptosis in MCF-7 cells. Amentoflavone also inhibited invasion and migration of A549 and HT29 cancer cells. The combination with doxorubicin indicates that Selaginella and amentoflavone extracts could increase the anticancer effects of doxorubicin in vivo by decreasing the tumor volume in the cancer cell-induced animals. These results demonstrate Selaginella's potential as a chemotherapeutic agent to enhance the anticancer effects of doxorubicin. Nevertheless, further research is necessary to have more insights and evidence regarding its activity.